Nomenclature of Chinese street food names in Malaysia: A scalar analysis - Zhu, Hongxiang; Lay, Hoon Ang; Mansor, Nor Shahila; Kai, Chee Lam (SAGE Publications, 2023)
This study examines how the nomenclature of street food names includes trans-local, trans-regional, and trans-national scales in local language resources. The study adopts a qualitative case study on street food names in Malaysia. The study sample comprised 856 street food names collected in Kuala Lumpur. The food nomenclature framework and the concepts of trans-local, trans-regional, and trans-national scales were adopted to elicit the data. It was found that: (i) there are more complex combinations based on ingredient, cooking method, food attribute, commemorative aspect, and good name; (ii) there are scale-making ways, via the presentation and the transliteration of street food elements. In conclusion, the nomenclature of street food names labels Malaysia as a multiscalar locality in which trans-local, trans-regional, and trans-national scales can be discerned. Thus, this study reveals how nomenclature shapes and is shaped by geographical scales. Therefore, it contributes to the nomenclature of food and place marketing.